• :00Days
• :00Hours
• :00Mins
• 00Seconds
A new era for learning is coming soon Suggested languages for you:

Europe

Answers without the blur. Sign up and see all textbooks for free! Q6.

Expert-verified Found in: Page 127 ### Pre-algebra

Book edition Common Core Edition
Author(s) Ron Larson, Laurie Boswell, Timothy D. Kanold, Lee Stiff
Pages 183 pages
ISBN 9780547587776 # Solve the equation. Check your solution.$\mathbf{3}\left(\mathbf{x}\mathbf{+}\mathbf{1}\right)\mathbf{=}\mathbf{6}$

The solution for the equation $3\left(x+1\right)=6$ is$x=1$ .

See the step by step solution

## Step 1 – Separate the variable and constants

Write the original equation and separate the variable and constants.

$\begin{array}{c}3\left(x+1\right)=6\\ 3x+3=6\\ 3x+3-3=6-3\\ 3x=3\end{array}$

## Step 2 – Solve for x

Now, divide both sides of the equation by 1.

$\begin{array}{c}\frac{3x}{3}=\frac{3}{3}\\ x=1\end{array}$

Therefore, the solution of the equation is$x=1$ .

## Step 3 – Check the solution

To check the solution, write the original equation and substitute the value of x.

$3\left(x+1\right)=6$

Now, substitute$x=1$and check the result.

$\begin{array}{c}3\left(1+1\right)=6\\ 3\left(2\right)=6\\ 6=6\end{array}$

As the left-hand side is equal to right hand side, this signifies that the solution is correct. ### Want to see more solutions like these? 